Associations between sexual stigma, enacted HIV stigma, internalized HIV stigma and homonegativity, and depression: testing an extended minority stress model among men who have sex with men living with HIV in India. Issue 12 (2nd December 2022) - Chakrapani, Venkatesan; Kershaw, Trace; Kaur, Jasvir; Shunmugam, Murali; Nelson, Ruban; Vijin, Pandara Purayil; Rajan, Magesh; Subramanian, Thilakavathi
ABSTRACT: Limited data is available on the associations between intersectional stigmas and mental health outcomes among men who have sex with men living with HIV (MSMLH) in India. The minority stress model postulates that sexual stigma contributes to depression through proximal stressors like internalized homonegativity (IHN). Using cross-sectional survey data from 119 MSMLH in 2015/16, we tested whether: (1) sexual stigma and enacted HIV stigma (EHS) are associated with depression; (2) their effects on depression are mediated through IHN and internalized HIV stigma (IHS); and (3) their effects on IHN are mediated through IHS. Significant direct associations were observed between scores on sexual stigma and IHS ( β = .49, 95% CI .27, .70), EHS and IHN ( β = .19, 95% CI .03, .36), and IHS and IHN ( β = .07, 95% CI .03, .12). IHS scores mediated the associations of sexual stigma with depression ( β = .17, 95% CI .07, .27) and IHN scores ( β = .04, 95% CI .004, .07). EHS was not found to be significantly associated with depression or IHN. The findings partially support the minority stress model among MSMLH and highlight the importance of addressing both sexual and HIV-related stigmas to improve mental health of MSMLH, especially by screening for and reducing IHS, IHN and depression.